PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS X MIA 7 SMA NEGERI 1 PEKANBARU - Chintia Ramadhona; Armis '; Syofni ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :The purpose of this research is to improve the learning process and to improve mathematics achievement by applying problem based learning. The research is classroom action research that consist of two cycles and at the end of every cycle carried out mathematics achievement test . The subject of this research is students of class X MIA 7 SMAN 1 Pekanbaru in the first semester academic years 2014/2015, there are 28 students in the class, consist of 11 boys and 17 girls who have heterogeneous academic ability. Data collecting through observation and written test. The observation was doing for the observation of learning activity of teacher and students, student attitude and student skill. While written test is to evaluate student’s knowledge. Based on the analysis of the activity of teacher and students, the application of the problem besed learning is getting better Based on the result of analysis, the amount of student that reaching minimum completeness criteria for cooperation attitude increase from 42,85% at early score to 67,85% at the first cycle and 96,42% at the second cycle. For discipline attitude increases from 57,14% at early scor to 71,42% at the first cycle and 100% at the second cycle. For honesty attitude increase from 53,37% at early score to 71,42% at the first cycle and 100% at the second cycle. For tolerance attitude increase from 46,42% at early score to 71,42% at the first cycle and 96,42% at the second cycle. The amount of student that reaching minimum completeness criteria for skill interest increase from 50% at early score to 92,84% at the first cycle and 100% at the second cycle. The amount of student that reaching minimum completeness criteria for knowledge interest increase from 7,14% at early score to 92,84% at the first cycle and 100% at the second cycle. The result of research conclude that problem based learning can improve the learning process and improve mathematics achievement of X MIA 7 SMAN 1 Pekanbaru in the first semester academic years 2014/2015.Keywords : Mathematics learning outcome, Problem Based Learning, Class action research.